The controllable electron-heating by external magnetic fields at relativistic laser-solid interactions in the presence of large scale pre-plasmas. (24th April 2017) - Wu, D; Luan, S X; Wang, J W; Yu, W; Gong, J X; Cao, L H; Zheng, C Y; He, X T
Abstract: The two-stage electron acceleration/heating model (Wu et al 2017 Nucl. Fusion 57 016007 and Wu et al 2016 Phys. Plasmas 23 123116) is extended to the study of laser magnetized-plasmas interactions at relativistic intensities and in the presence of large-scale preformed plasmas. It is shown that the electron-heating efficiency is a controllable value by the external magnetic fields. Detailed studies indicate that for a right-hand circularly polarized laser, the electron heating efficiency depends on both strength and directions of external magnetic fields. The electron-heating is dramatically enhanced when the external magnetic field is of B ≡ ω c / ω 0 > 1 . When magnetic field is of negative direction, i.e. B < 0, it trends to suppress the electron heating. The underlining physics—the dependences of electron-heating on both the strength and directions of the external magnetic fields—is uncovered. With − ∞ < B < 1, the electron-heating is explained by the synergetic effects by longitudinal charge separation electric field and the reflected 'envelop-modulated' CP laser. It is indicated that the 'modulation depth' of reflected CP laser is significantly determined by the external magnetic fields, which will in turn influence the efficiency of the electron-heating. While with B > 1, a laser front sharpening mechanism is identified at relativistic laser magnetized-plasmas interactions, which is responsible for the dramatical enhancement of electron-heating.